INTERMEDIATING ROLES OF INSTITUTIONAL INFRASTRUCTURE IN THE TRADE OPENNESS-INCLUSIVE GROWTH NEXUS: NEW EMPIRICAL EVIDENCE FROM NIGERIA - Ajayi, Felix Odunayo; Ogede, Jimoh Sina; Siyanbola, Adedamola Akeem; Atoyebi, Olayinka Esther; Yinusa, Olumuyiwa Ganiyu (Jurnal Ekonomi dan Bisnis Airlangga, 2024)
Introduction: Inclusive growth (IG) is a revolutionary method for generating and sustaining macroeconomic stability through economic development, social equity, and prosperity. There has been little theoretical and empirical study in Nigeria on analyzing the effects of trade openness on inclusive growth and exploring its determinants. Methods: This study examines the intermediating roles of institutional infrastructure in the trade openness-inclusive growth nexus in Nigeria spanning from 1985 to 2021. The study employed the Johansen Cointegration methodology to confirm the existence of the long-run association while fully modified ordinary least squares (FM-OLS) and dynamic ordinary least squares (DOLS) techniques are used to elucidate the uncertainty in the trade openness-inclusive growth nexus. Results: Consequently, the results of the Johansen Cointegration confirmed the long-run association among variables. The FM-OLS and D-OLS indicate that trade openness enhances growth in Nigeria, suggesting that greater trade openness would foster inclusive growth and remain a focal point for both direct and indirect relations with inclusive growth. The interaction effects of trade openness and institutional infrastructure on inclusive growth show negative and insignificant effects on inclusive growth, demonstrating that institutional infrastructure plays a mitigating influence in the relationship between trade openness and inclusive growth, albeit insignificant at a 5% level. Conclusion and suggestion: The study recommends that Nigeria should pursue policies aimed at improving institutional infrastructures with a way of reducing transactional costs and risks related to trading.